ACHIEVEMENT OF THE STATE INDEPENDENCE IN UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The achievement of state independence in Uzbekistan on September 1, 1991, marked a transformative moment in the nation's history, following the dissolution of the Soviet Union. This article explores the historical context, key events, and the subsequent impact of Uzbekistan's independence. It highlights the declaration of sovereignty, the pivotal role of President Islam Karimov, and the country's journey towards international recognition. Post-independence, Uzbekistan undertook significant political and economic reforms, while also experiencing a cultural revival. Despite challenges such as political repression and economic disparities, recent reforms under President Shavkat Mirziyoyev indicate progress towards liberalization and modernization. Uzbekistan's path since 1991 reflects its resilience and aspiration to build a strong, independent nation with a promising future.